Evaluation of the evidence of the remuneration of the administrators and the levels of corporate governance (Revista Brasileira de Contabilidade e Gestão, 2016)
Corporate governance has emerged as proposed minimization of conflicts and costs of agency problem. This essay has the objective to verify what is the status of the disclosure about administrators remuneration in Brazilian companies listed in BM&FBOVESPA with bigger and smaller level of corporate governance, based on the European evaluation model indicated by Ferrarini, Maloney and Ungureanu (2009). This essay is a descriptive study as for the objectives; as for the technical procedures, it is considered as documental research based on data obtained from the Reference Form of the BM&FBOVESPA listed companies. As for the approach of the problem, it is presented as a quantitative study with hypothesis test application test t of Student. The sample of the research is of 20 companies, 10 from the New Market corporative governance segment and the other 10 from the Traditional segment. The results of the essay show a higher level of disclosure in companies from the New Market for governance, and individual examples of executives and non-executives, whereas for the political area, the disclosure is found in similar level.
Keywords: corporate governance; managers remuneration; disclosure